N-glycosylation state of TRPM8 protein revealed by terahertz spectroscopy and molecular modelling - Mernea, Maria; Ulăreanu, Roxana; Călboreanu, Octavian; Chirițoiu, Gabriela; Cucu, Dana; Mihăilescu, Dan F. (Biochimica et biophysica acta. General subjects, 2020)
TRPM8 member of the TRP superfamily of membrane proteins participates to various cellular processes ranging from Ca2+ uptake and cold sensation to cellular proliferation and migration. TRPM8 is a large tetrameric protein with more than 70% of its residues located in the cytoplasm. TRPM8 is N-glycosylated, with a single site per subunit. This work focuses on the N-glycosylation of TRPM8 channel that was previously studied by our group in relation to proliferation and migration of tumoral cells. Here, experimental data performed with deglycosylating agents assess that the sole glycosylation site contains complex glycans with a molecular weight of 2.5 kDa. The glycosylation state of TRPM8 in cells untreated and treated with a deglycosylating agent was addressed with Terahertz (THz) spectroscopy. Results show a clear difference between cells comprising glycosylated and deglycosylated TRPM8, the first presenting an increased THz absorption. Human TRPM8 was modelled using as templates the available TRPM8 and other TRPM channels structures. Glycosylations were modelled by considering two glycan structures with molecular weight close to the experiment: shorter and branched at the first sugar unit (glc1) and longer and unbranched (glc2). Simulation of THz spectra based on the molecular dynamics of unglycosylated and the two glycosylated TRPM8 models in lipid membrane and solvation box showed that glycan structure strongly influences the THz spectrum of the channel and of other components from the simulation system. Only spectra of TRPM8 with glc1 glycans were in agreement with the experiment, leading to the validation of glc1 glycan structure. •The glycosylation state of TRPM8 in cells was addressed with THz spectroscopy.•Cells with glycosylated vs. un-glycosylated TRPM8 present a higher THz absorbance.•Human TRPM8 was modelled based on available TRPM8 and TRPM channels structures.•Channel glycosylations were modelled by considering two glycan structures.•A glycosylated TRPM8 model was validated on the agreement with the experiment.